LITERATURE OF THE TRANSGENDER: SENSITIZING ISSUES OF TRANS VIOLENCE AND VICTIMIZATION (International Journal of Food and Nutritional Sciences, 2022)
Transgender literature as a genre has emerged significantly in recent years and has paved the way for trans activism. Literature of the transgender has moved a long way in sensitizing issues and the problems of transgender identity and discrimination. Transgender writers have started to represent transsexuality, trans violence and victimization of the transgender community. Literature of the transgender portrays the life of transgender people who undergo an identity crisis in identifying themselves as bigender, pangender, gender queer, non-binary, agender, androgynous or other gender. Transgender writers across the world have been physically, verbally or sexually assaulted, abandoned and discriminated by the mainstream, and to reveal the social stigma that is existing the transgender writers have chosen writing as a media to expose their vulnerability. The aim of this article is to sensitize the issues of victimization and the prevailing trans violence towards transgender community. It also tries to break the stereotypical barriers associated with the transgender community. The books of various transgender writers across the globe is analyzed to explore the history of transgender such as transphobic harassment, lack of legal protection and problems regarding identity documents, health issues and transgender violence across the globe.